A Smooth Forwarding Operation in Wireless Mesh Network - Gannapathy, Vigneswara Rao; Suaidi, Mohamad Kadim; Johal, Muhammad Syahrir; Lim, Kim Chuan (2011)
The IEEE 802.11 Distributed Coordination Function (DCF) Medium Access Control (MAC) protocol is designed to efficiently facilitate the limited communication bandwidth of wireless channel. This protocol uses Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) mechanism. This mechanism continues suffer from throughput degradation when directly applied in multihop Wireless Mesh Network (WMN). The major reason for this poor performance is due to larger signaling overheads (RTS and CTS signaling packet) introduced in order to forward a single data packet in multihop WMN. This inefficient forwarding operation caused the throughput degradation signifficantly. Therefore, an efficient forwarding operation is proposed in this paper to reduce the amount of signaling overheads which are needed to forward a single packet in multihop WMN. The proposed protocol uses the capability of overhearing in order to forward the data packet from one hop to another hop. This process will continue until the data packet reaches the respective destination. As a result, the enhanced protocol reduces the latency caused by signaling thus improve its throughput in multihop WMN. The multihop network performances are evaluated analytically in terms of throughput and delay. Through the simulation, it is proven that the proposed protocol provides significant improvement in throughput and delay. The results show that the proposed protocol outperforms the existing IEEE DCF MAC protocol when it is evaluated in multihop WMN.